Multifunctional layered magnetic composites - Siglreitmeier, Maria; Wu, Baohu; Kollmann, Tina; Neubauer, Martin; Nagy, Gergely; Schwahn, Dietmar; Pipich, Vitaliy; Faivre, Damien; Zahn, Dirk; Fery, Andreas; Cölfen, Helmut (Beilstein Journal of Nanotechnology, 2015)
A fabrication method of a multifunctional hybrid material is achieved by using the insoluble organic nacre matrix of the Haliotis laevigata shell infiltrated with gelatin as a confined reaction environment. Inside this organic scaffold magnetite nanoparticles (MNPs) are synthesized. The amount of MNPs can be controlled through the synthesis protocol therefore mineral loadings starting from 15 wt % up to 65 wt % can be realized. The demineralized organic nacre matrix is characterized by small-angle and very-small-angle neutron scattering (SANS and VSANS) showing an unchanged organic matrix structure after demineralization compared to the original mineralized nacre reference. Light microscopy and confocal laser scanning microscopy studies of stained samples show the presence of insoluble proteins at the chitin surface but not between the chitin layers. Successful and homogeneous gelatin infiltration in between the chitin layers can be shown. The hybrid material is characterized by TEM and shows a layered structure filled with MNPs with a size of around 10 nm. Magnetic analysis of the material demonstrates superparamagnetic behavior as characteristic for the particle size. Simulation studies show the potential of collagen and chitin to act as nucleators, where there is a slight preference of chitin over collagen as a nucleator for magnetite. Colloidal-probe AFM measurements demonstrate that introduction of a ferrogel into the chitin matrix leads to a certain increase in the stiffness of the composite material.
Keywords: bio-inspired mineralization; biomineralization; chitin; ferrogel; hybrid materials; magnetite; nacre